1997
DOI: 10.1021/bi971478r
|View full text |Cite
|
Sign up to set email alerts
|

The Escherichia coli FOF1 γM23K Uncoupling Mutant Has a Higher K0.5 for Pi. Transition State Analysis of This Mutant and Others Reveals That Synthesis and Hydrolysis Utilize the Same Kinetic Pathway

Abstract: The Escherichia coli FOF1 ATP synthase uncoupling mutation, gammaM23K, was found to increase the energy of interaction between gamma and beta subunits, prevent the proper utilization of binding energy to drive catalysis, and block the enzyme in a Pi release mode. In this paper, the effects of this mutation on substrate binding in cooperative ATP synthesis are assessed. Activation of ATP synthesis by ADP and Pi was determined for the gammaM23K FOF1. The K0.5 for ADP was not affected, but K0.5 for Pi was approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
80
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(92 citation statements)
references
References 53 publications
11
80
1
Order By: Relevance
“…For a given reaction series that uses the same transition state there should be a quantitative relationship between enthalpy and entropy of activation, such as an isokinetic relationship [54]. We previously demonstrated that the transitionstate thermodynamic parameters from ATP synthases with a variety of mutations or from different sources could be fitted to an isokinetic line [43,45] such as that shown in Figure 5. In isokinetic relationships there is a linear free-energy relationship between two rate constants (k " and k # ) measured at two temperatures (T # T " ), which can be given by the equation : log k # l ajb log k " where a and b are constants [54].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For a given reaction series that uses the same transition state there should be a quantitative relationship between enthalpy and entropy of activation, such as an isokinetic relationship [54]. We previously demonstrated that the transitionstate thermodynamic parameters from ATP synthases with a variety of mutations or from different sources could be fitted to an isokinetic line [43,45] such as that shown in Figure 5. In isokinetic relationships there is a linear free-energy relationship between two rate constants (k " and k # ) measured at two temperatures (T # T " ), which can be given by the equation : log k # l ajb log k " where a and b are constants [54].…”
Section: Discussionmentioning
confidence: 99%
“…The conditions for the ACMA assay were optimized for maximal sensitivity and are detailed in the legend to Figure 3. ATP hydrolysis rates were determined at 30 mC in a buffer containing 50 mM Hepes\KOH, 10 mM ATP, 5 mM MgSO % and 1 µM carbonyl cyanide mchlorophenylhydrazone (CCCP), pH 7.5, with 5 mM phosphoenolpyruvate, 50 µg\ml pyruvate kinase and 0.1-0.3 mg\ml membrane protein [45]. For the Arrhenius analysis, the pH was adjusted to 7.5 at the appropriate temperature [43].…”
Section: Enzymic Assaysmentioning
confidence: 99%
See 3 more Smart Citations